منهج تعليم اللغة العربية في المعاهد الدينية - Nurdin, Nurdin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Arabic language is an important language for Moslems all over the words, since it becomes the tool to understand Al-Qur’an and Hadits. In teaching Arabic, the teachers need to use various teaching methods as one of the pivotal parts in the teaching and learning process. This article describes the teaching and learning Arabic in the first, second, and third grad of Tsanawiyah and Aliyah and the teaching methods used, such as: reading and translation, memorizing, and vocabulary building. Those teaching methods are used to improve the students’ achievement in learning Arabic in each level.